Complaints of Low Back Pain in Tailors - Santy Deasy Siregar; Putranto Manalu; Rapael Ginting; Victor Trismanjaya Hulu; Jeremia Chandra Partogi Siallagan (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Low back pain (LBP) is one of the musculoskeletal disorders as a result of incorrect ergonomics. The impact caused by low back pain is bad posture, stiffness, pinched nerve, and muscle weakness. This study aims to determine the relationship between ages, years of service, length of sitting, work posture, and the chair’s ergonomics with complaints of low back pain in tailors at Pasar Petisah, Kota Medan, with 35 workers based on inclusion and exclusion criteria. The research tools are interviews, observations, and filling out questionnaires. This sampling technique is used purposive sampling methods. Data were analyzed using the STATCAL application with a 5% chi-square test. Based on the result, we concluded that there is a long relationship between ages (p=0,02), years of service (p=0,04), length of sitting (p=0,01), and work posture (p=0,03) with the occurrence of low back pain tailors. Tailors in the Petisah Market in Medan City are at risk for complaints of low back pain based on age, long years of service, a risky length of sitting, and a risky work posture. If the workers ignore low back pain, the impact is the emergence of serious problems such as stiffness in the spine, fractures, pinched nerves, and can even cause death.